The Viral Polymerase Complex Mediates the Interaction of Viral Ribonucleoprotein Complexes with Recycling Endosomes during Sendai Virus Assembly - Emmanuelle Genoyer (American Society for Microbiology, 2020)
ABSTRACT Paramyxoviruses are negative-sense single-stranded RNA viruses that comprise many important human and animal pathogens, including human parainfluenza viruses. These viruses bud from the plasma membrane of infected cells after the viral ribonucleoprotein complex (vRNP) is transported from the cytoplasm to the cell membrane via Rab11a-marked recycling endosomes. The viral proteins that are critical for mediating this important initial step in viral assembly are unknown. Here, we used the model paramyxovirus, murine parainfluenza virus 1, or Sendai virus (SeV), to investigate the roles of viral proteins in Rab11a-driven virion assembly. We previously reported that infection with SeV containing high levels of copy-back defective viral genomes (DVGs) (DVG-high SeV) generates heterogenous populations of cells. Cells enriched in full-length (FL) virus produce viral particles containing standard or defective viral genomes, while cells enriched in DVGs do not, despite high levels of defective viral genome replication. Here, we took advantage of this heterogenous cell phenotype to identify proteins that mediate interaction of vRNPs with Rab11a. We examined the roles of matrix protein and nucleoprotein and determined that their presence is not sufficient to drive interaction of vRNPs with recycling endosomes. Using a combination of mass spectrometry and comparative analyses of protein abundance and localization in DVG-high and FL-virus-high (FL-high) cells, we identified viral polymerase complex component protein L and, specifically, its cofactor C as interactors with Rab11a. We found that accumulation of L and C proteins within the cell is the defining feature that differentiates cells that proceed to viral egress from cells containing viruses that remain in replication phases. IMPORTANCE Paramyxoviruses are members of a family of viruses that include a number of pathogens imposing significant burdens on human health. In particular, human parainfluenza viruses are an important cause of pneumonia and bronchiolitis in children for which there are no vaccines or directly acting antivirals. These cytoplasmic replicating viruses bud from the plasma membrane and co-opt cellular endosomal recycling pathways to traffic viral ribonucleoprotein complexes from the cytoplasm to the membrane of infected cells. The viral proteins required for viral engagement with the recycling endosome pathway are still not known. Here, we used the model paramyxovirus Sendai virus, or murine parainfluenza virus 1, to investigate the role of viral proteins in this initial step of viral assembly. We found that the viral polymerase components large protein L and accessory protein C are necessary for engagement with recycling endosomes. These findings are important in identifying viral proteins as potential targets for development of antivirals.